Gases, Liquids and Solids and other States of Matter - Tabor D. (Cambridge, Cambridge University Press, 2000)
There are new sections on amorphous solids and liquid crystals, and completely new chapters on colloids and polymers.Using unsophisticated mathematics and simple models, Professor Tabor leads the reader skilfully and systematically from the basic physics of interatomic and intermolecular forces, temperature, heat and thermodynamics, to a coherent understanding of the bulk properties of gases, liquids and solids. The introductory material on intermolecular forces and on heat and thermodynamics is followed by several chapters dealing with the properties of ideal and real gases, both at an elementary and at a more sophisticated level. The mechanical, thermal and electrical properties of solids are considered next, before an examination of-the liquid state. The author continues with chapters on colloids and polymers, and ends with a discussion of the dielectric and magnetic properties of matter in terms of simple atomic models. The abiding theme is that all these macroscopic material properties can be understood as resulting from the competition between thermal energy and intermolecular or interatomic forces. This is a lucid textbook which will continue to provide students of physics and chemistry with a comprehensive and integrated view of the properties of matter in all its many fascinating forms.